GUIDE FOR THE PREPARATION OF THE SURGICAL PATIENT FOR HOSPITAL DISCHARGE: VALIDATION OF CARE-EDUCATIONAL TECHNOLOGY - Nietsche, Elisabeta Albertina; Colussi, Giovana; Salbego, Cléton; Cogo, Silvana Bastos; Ramos, Tierle Kosloski; Girardon- Perlini, Nara Marilene Oliveira; Sehnem, Graciela Dutra (Cogitare Enfermagem, 2024)
Objective: Validate the content of a care-educational technology in the form of a guide aimed at preparing the surgical patient and their companion for hospital discharge. Method: The methodological study was conducted between February 2019 and December 2021 in Santa Maria-RS-Brazil. 22 specialists in nursing, physiotherapy, and nutrition participated. The analysis took place using the Content Validity Index. The data were collected online and processed using descriptive and analytical statistics. Results: The guide obtained a validity of 0.81. Your content is intended for surgical patients and companions under the mediation of the healthcare professional. The guide contains care for surgical wounds, gastric and enteric tubes, stomas, and bladder catheterizations. Adjustments were made regarding the language, text objectivity, removal of technical terms, and review of the images. Conclusion: According to experts, the guide comprises a valid technology to be used by professionals in health education with the surgical patient and their companions.